2004
DOI: 10.1182/blood-2003-12-4438
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytotoxicity of allogeneic NK cells with killer immunoglobulin-like receptor ligand incompatibility against melanoma and renal cell carcinoma cells

Abstract: IntroductionNatural killer (NK) cells have antigen-independent tumor cytotoxicity and have been shown in murine models to control and prevent tumor growth and dissemination. 1,2 However, the exact role that NK cells play in the control of cancer in humans remains a matter of controversy.NK cells do not rearrange genes coding for specific antigen receptors; rather, their recognition of targets is regulated through a balance of activating or inhibitory signals. 3 It is necessary to inactivate NK cells to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 41 publications
(44 reference statements)
3
95
1
1
Order By: Relevance
“…It has been shown that donor T cells are indeed crucial for recovery of immune function after haploidentical transplantations. 49 Adding KGF treatment to haploidentical transplantations, possibly in combination with standard GVHD prophylaxis, 50 might therefore be a valuable clinical option, allowing more transplantations to be performed safely without serious GVHD and immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that donor T cells are indeed crucial for recovery of immune function after haploidentical transplantations. 49 Adding KGF treatment to haploidentical transplantations, possibly in combination with standard GVHD prophylaxis, 50 might therefore be a valuable clinical option, allowing more transplantations to be performed safely without serious GVHD and immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report (72) demonstrates that KIR-incompatible allogeneic NK cells have superior antitumor effects against fresh tumor cells isolated from different solid cancers, as well as against MEL and RCC established tumor cell lines (73). Interactions between solid tumor cells and the microenvironment in vivo create a context that promotes tumor growth, selection, and protection from immune attack, suggesting that the tridimensional architecture of solid cancer lesions is likely one of the tumor mechanisms to escape immunosurveillance (70).…”
Section: Nk Cell-based Immunotherapeutic Strategies Against Cancermentioning
confidence: 99%
“…Some encouraging data comes from work with solid tumors. 49 Whether NK cells will be used without additional manipulation, or whether stimulation and culture either short or medium term with cytokines such as IL-2 will prove to be more effective awaits further studies. 50 Purging and enrichment technology using magnetic beads for clinical application is technologically fascinating but expensive, in direct costs of antibodies and columns and the time of laboratory personnel.…”
Section: Future Prospectsmentioning
confidence: 99%